2017
DOI: 10.1371/journal.pone.0174641
|View full text |Cite
|
Sign up to set email alerts
|

Correction of confidence intervals in excess relative risk models using Monte Carlo dosimetry systems with shared errors

Abstract: In epidemiological studies, exposures of interest are often measured with uncertainties, which may be independent or correlated. Independent errors can often be characterized relatively easily while correlated measurement errors have shared and hierarchical components that complicate the description of their structure. For some important studies, Monte Carlo dosimetry systems that provide multiple realizations of exposure estimates have been used to represent such complex error structures. While the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…Although we found that shared additive error was larger in magnitude than SMME, we focused our analysis on SMME as other work has indicated minimal influence of shared additive error on epidemiological results in a Berkson model ( Zhang et al, 2017 ). Shared error differs from traditional measurement error as the errors are not independent, which is common in air pollution exposure models because (1) model covariates are usually aggregated in time and space and (2) air pollution exhibits finely resolved variability through time and space.…”
Section: Discussionmentioning
confidence: 99%
“…Although we found that shared additive error was larger in magnitude than SMME, we focused our analysis on SMME as other work has indicated minimal influence of shared additive error on epidemiological results in a Berkson model ( Zhang et al, 2017 ). Shared error differs from traditional measurement error as the errors are not independent, which is common in air pollution exposure models because (1) model covariates are usually aggregated in time and space and (2) air pollution exhibits finely resolved variability through time and space.…”
Section: Discussionmentioning
confidence: 99%
“…However, uncertainties in average organ doses will be assumed to be statistically independent across the three periods; i.e., uncertain doses to individuals in different periods will be assumed to be uncorrelated. This approach to accounting for uncertainty is intended to provide unbiased estimates of risk with appropriately broad confidence intervals (e.g., Kwon et al 2016 ; Zhang et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other methods have been developed to account for uncertainties in exposure estimation in epidemiological studies at the stage of data analysis. Zhang et al (2017) described a corrected confidence interval (CCI) approach to correct inflated variances of risk parameters estimated by the Poisson regression model due to uncertainties in the dosimetry system [57]. The CCI approximates an asymptotic distribution of parameter estimates in Poisson ERR model using multiple exposure vectors from the Monte Carlo dosimetry system.…”
Section: Discussionmentioning
confidence: 99%